Speech text of the Malaysia data innovation talent X DOSM Datathon 2023 (MDIT X DD 2023) / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
Keep in mind that MDIT X DD 2023 is not merely a competition. It serves as a platform for Innovation and Data Analysis. Your dedication to the Sustainable Development Goals is truly commendable and we are proud to support you.